Investment cycles - Kirkpatrick, Charles D., II (FT Press Delivers elements., 2011)
"This Element is an excerpt from Technical analysis: the complete resource for financial market technicians, second edition (ISBN: 9780137059447) by Charles D. Kirkpatrick III, CMT, and Julie Dahlquist. Do price cycles come in waves? An objective look at the evidence-and what it means to investors."--Resource description page.